Reasons of identity a normative guide to the political and legal assessment of identity claims - Eisenberg, Avigail I., 1962- (Oxford : Oxford University Press, 2009)
The current legal and political context is more congenial than ever to considering claims made by minorities for the protection of some aspect of their identity. This book argues that multicultural societies depend for their success on having courts and legislatures which are capable of assessing these identity claims fairly.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Multiculturalism -- Political aspects; Multiculturalism -- Law and legislation; Minorities; Minorities -- Legal status, laws, etc; Minorities -- Civil rights